2010
DOI: 10.3171/2010.5.focus10109
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation compared with bariatric surgery for the treatment of morbid obesity: a decision analysis study

Abstract: Object Roux-en-Y gastric bypass is the gold standard treatment for morbid obesity, although failure rates may be high, particularly in patients with a BMI > 50 kg/m2. With improved understanding of the neuropsychiatric basis of obesity, deep brain stimulation (DBS) offers a less invasive and reversible alternative to available surgical treatments. In this decision analysis, the authors determined the success rate at which DBS would be equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 122 publications
0
32
0
1
Order By: Relevance
“…Furthermore, animal studies have demonstrated that the ventromedial and lateral hypothalamus are implicated in the regulation of feeding and energy metabolism and therefore considered as possible targets for clinical DBS aimed at treating morbid obesity [1,2,3,4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, animal studies have demonstrated that the ventromedial and lateral hypothalamus are implicated in the regulation of feeding and energy metabolism and therefore considered as possible targets for clinical DBS aimed at treating morbid obesity [1,2,3,4]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic neuromodulation for obesity control has been considered ever since the rise and fall of the simplistic dual center model which hypothesized that control of eating resided in the interaction between ventromedial hypothalamic satiety and lateral hypothalamic feeding centers [1,2,3,4]. However, due to the functional complexity and closely adjoined nervous structures in the hypothalamus, therapeutic beneficial hypothalamic deep brain stimulation (DBS) may in addition influence normal central homeostatic control, due to the involvement of overlapping limbic and autonomic networks.…”
Section: Introductionmentioning
confidence: 99%
“…Pisapia et al conducted a decision analysis comparing the two major surgical options for obesity: laparoscopic Roux-en-Y gastric bypass and laparoscopic adjustable gastric banding. 65 Laparoscopic banding was found to not be effective at achieving successful weight loss (defined as at least 45% of excess weight), and the complication rates for gastric bypass surgery (33%) far exceeded those of DBS (19%). These reports characterize DBS in obesity as a promising therapeutic avenue from an economic standpoint.…”
Section: Cost and Ethical Considerations Of Dbs Cost Considerationsmentioning
confidence: 99%
“…While gastric bypass is currently the gold standard therapy for morbid obesity, a recent study used decision analysis to note that DBS for obesity would only need an 83% success rate to achieve equivalence to bypass surgery. 162 Anorexia nervosa is another psychiatric disorder involving limbic circuits. Up to 70% of patients suffering from anorexia have a chronic refractory course, and it is one of the deadliest psychiatric disorders, with a mortality rate of 10%.…”
Section: Obesity and Anorexiamentioning
confidence: 99%